Convex Polyhedron Method to Stability of Continuous Systems with Two Additive Time-Varying Delay Components - Tiejun Li; Junkang Tian (Journal of Applied Mathematics)
This paper is concerned with delay-dependent stability for continuous systems with two additive time-varying delay components. By constructing a new class of Lyapunov functional and using a new convex polyhedron method, a new delay-dependent stability criterion is derived in terms of linear matrix inequalities. The obtained stability criterion is less conservative than some existing ones. Finally, numerical examples are given to illustrate the effectiveness of the proposed method.